Design of Earthquake Disaster Evacuation Route Simulation in a High-Storey Building Using Virtual Reality - Masdhana, Bagus Wahyu; Tranggono, Tranggono (Journal La Multiapp, 2024)
Indonesia is a country located in the Pacific Ring of Fire, because of this Indonesia is vulnerable to earthquakes because it is located at the meeting point of several colliding tectonic plates. In addition, the presence of active volcanoes is also an additional factor. The construction of high-rise buildings in Indonesia has continued to increase in recent years along with the growth of urbanization and the need for more efficient space in urban areas, this has increased the risk of accidents in high-rise buildings. With these problems, a disaster simulation is needed which can be the right step to understand the correct ways to handle and evacuate from disasters. The right simulation for this problem is to use Virtual Reality (VR)-based learning because this simulation can increase the effectiveness of disaster management education by experiencing firsthand a realistic and interactive earthquake scenario simulation. The results of the pre-post test processed using the Wilcoxon signed rank test method obtained a result of 7.5 where 7.5 ≤ 52 (critical value) concluded that this simulation provides a significant change in knowledge of earthquake disaster mitigation in high-rise buildings. And from the SUS (System Usability Scale) Questionnaire, the score obtained was 78.875 which is included in the category 70-85 which means that this system is quite good in terms of usability. Users generally feel comfortable using the system.